Analisis Daya Dukung Lahan Perkebunan di Kabupaten Garut Provinsi Jawa Barat - Ayu Handayani; Yulia Indri Astuty; Brigitta Maria Rumondor; Fani Setyawan (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
Garut Regency produces agricultural and plantation commodities that support the city's and surrounding districts' food needs. On the other hand, Garut Regency is also experiencing a positive population growth rate from 2010 to 2020. This increase in growth rate has implications for several problems, one of which is the increasing land conversion from agricultural land to built-up land. This increase in land use change causes the ability of land to complement plantation commodities to decrease. This study aims to analyze the carrying capacity of plantation land and the variety of commodities in the carrying capacity of plantation land in the surplus category. RTRW and elevation of the carrying capacity of plantation land in Garut Regency using descriptive methods with analysis of land carrying capacity. Surplus and six sub-districts experienced a deficit in the land's carrying capacity, and the tobacco commodity became the leading commodity in all sub-districts. Based on the RTRW and elevation of the carrying capacity of land allotted for plantations, the most extensive is in the Cibalong sub-district, with an area of ​​around 33.97% with a very high surplus category. The location (ha) in the type of reduction to elevation is the highest, with a spread between 250-2000 masl in Bungbulang District. This research is hoped to be used as material input in land policies in Garut Regency regarding regional planning and plantation commodities.